Perancangan Sistem Aplikasi Mobile Sebagai Pusat Informasi Bagi Mahasantri K.H Mas Mansyur Berbasis Android - Imaduddin, Helmi; , Agus Ulinuha, ST., MT., Ph.D (2015)
The very rapid development of science and technology makes information an important element in the development of the life today and certainly in foreseeable future. In an agency, the presentation of the quick and accurate information is urgently needed, as in the case in Islamic Boarding School K.H. Mas Mansur UMS. From the obtained information can be seen that there is a problem about the delivery of administrative and academic information from the boarding school to the students. Therefore, it requires an application that could provide solutions to this problem. The application that will be created in this is android-based application, because android is a complete platform started from the operating system, developer tools, applications market, mobile industry vendor support and the support of open system community. The design of android application using web service method begins with the stage of requirements analysis, data collection, and proceed with designing the application. The application that has been finished then tested to the students of Islamic Boarding School K.H. Mas Mansur UMS and obtained result that the application is very useful and facilitate the students in getting the relevant information related to the activity in the boarding school. Keywords: Android, Islamic Boarding School K.H. Mas Mansur, Information System